Facile extraction and characterization of cellulose nanocrystals from agricultural waste sugarcane straw. (22nd June 2021) - Lu, Shuyu; Ma, Tao; Hu, Xinna; Zhao, Jing; Liao, Xiaojun; Song, Yi; Hu, Xiaosong
Abstract: BACKGROUND: Sugarcane straw is an available but largely ignored lignocellulosic biomass to obtain cellulose nanocrystals (CNCs) with highly crystalline, tunable surface chemistries and a wide‐ranging adaptability. Herein, we utilized sugarcane straw to obtain pure cellulose via purification processes, followed by subsequent preparation of CNCs via sulfuric acid hydrolysis. The properties of the purified fibers and obtained CNCs were assessed by their composition, morphology, chemical structure, crystallinity and thermal stability. RESULTS: After the purification process, alkali‐treated fibers (ATFs) contained 886.33 ± 1.25 g kg −1 cellulose, and its morphological analysis revealed a smooth and slender fibrous structure. The CNCs obtained by treatment with 64 wt% sulfuric acid at 45 °C for 60 min were isolated in a yield of 21.8%, with a diameter and length of 6 to 10 nm and 160 to 200 nm, respectively. Moreover, crystallinity index of these CNCs reached 62.66%, and thermal stability underwent a two‐step degradation. Short‐term ultrasonication after hydrolysis was employed to enhance isolation of the CNC particles and improve the anionic charge with higher value −38.00 mV. CONCLUSION: Overall, isolation and characterization results indicated the potential for CNCs preparation using sugarcane straw, in addition to offering a fundamental understanding of this material and indicating potential applications. © 2021 Society of Chemical Industry.